2017
DOI: 10.15244/pjoes/64791
|View full text |Cite
|
Sign up to set email alerts
|

Waste Silica as a Valuable Component of Extensive Green-Roof Substrates

Abstract: Green roofs are becoming increasingly common practice of the urban sustainable environment. The growing substrate is the most important part of green-roof technology. The cost of engineering substrates can be reduced by using locally available components. Since green roofs are a relatively new concept in Poland, there is a need to examine substrate compositions and characteristics, including commonly used ingredients as well as alternative recycled/waste materials. The aim of our study was to assess the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It was hypothesised that Si could alleviate heavy metal toxicity in plant; hence, 5% silica fume additive was included in each formula of the growing media. Silicon can reduce active heavy metal ions in substrate, plant metal uptake, and root to shoot translocation [33][34][35][36]. The Ca-aggregate was taken from the Czatkowice Limestone Mine in Krzeszowice, and Zn-aggregate (mining waste rock fragments as well as flotation residues)-from the Boleslaw Mine and Metallurgical Plant in Bukowno near Olkusz.…”
Section: Materials and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…It was hypothesised that Si could alleviate heavy metal toxicity in plant; hence, 5% silica fume additive was included in each formula of the growing media. Silicon can reduce active heavy metal ions in substrate, plant metal uptake, and root to shoot translocation [33][34][35][36]. The Ca-aggregate was taken from the Czatkowice Limestone Mine in Krzeszowice, and Zn-aggregate (mining waste rock fragments as well as flotation residues)-from the Boleslaw Mine and Metallurgical Plant in Bukowno near Olkusz.…”
Section: Materials and Experimental Designmentioning
confidence: 99%
“…The high concentration of toxic metals might inhibit plant growth, reduce the content of chlorophyll, and damage root systems [43]. However, alkaline soil reaction limits the availability of trace elements for plants [34][35][36]. Symptoms of abnormal plant growth or excess of trace element in plants were not observed.…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These aggregates modify the micro-and mesoporosity of soils (Blouin et al 2013) and are more stable than other aggregates in soils (Jangorzo et al 2015). Furthermore, earthworms have an influence on the structure and the porosity of soils by their burrowing activities creating macropores whilst compressing the adjoining soil (Jangorzo et al 2015;Kooistra and Pulleman 2010). These influences on the physical structure consequently affect the hydraulic properties (Blouin et al 2013) and the water balance, i.e., infiltration, drainage, and evaporation, of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Asman et al 11 investigated the hydrological performance using rubber crumbs as drainage layer and proposed an optimum slope of 6% are suitable for lightweight green roofs. Krawczyk et al 12 identified waste silica as a valuable component of extensive green‐roof substrates, this material however is only available to a certain extent. Also Carson et al (2012) 13 put a focus on recycled and waste materials as GR substrates.…”
Section: Introductionmentioning
confidence: 99%